Perencanaan dan Perancangan Fasilitas Wisata Pertanian di Denpasar-Bali - I Made Handi Narayana Dita Handi; I Kadek Merta Wijaya; I Nyoman Warnata (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2022)
The design of agricultural tourism support facilities in Denpasar-Bali aims to restore the historical value it has as an agrarian area which makes agriculture the pulse of life which includes economic, sociological, and cultural aspects of the Balinese people as farmers and pays attention to the role of agriculture as a very complex multifunction with rural ecosystems. in Bali. This design is also an effort to conserve agricultural land or subak in Bali and as an introduction to new tourism objects in Denpasar which tend to lead to urban tourism. It is unfortunate that Bali is an agricultural area, but the rice fields are getting depleted with the development of tourism and the influence of fulfilling city functions where the level of rice consumption is still high, causing the government to implement a solution to import rice. Through a tourism architectural approach as an effort to develop agriculture to the public, technological and environmental approaches in the development of modern agriculture, as well as traditional and cultural approaches that have high magical values and have been passed down from generation to generation in Bali.